Optimized energy storage performance in NaNbO3-based ceramics via composition modification and micro-structure control. (1st May 2023) - Feng, Yao; Zhen, Yuhua; Jiang, Xiaolin; Yang, Zhengren; Qin, Zheng; Yang, Wenjie; Qie, Yuanyue; Geng, Hongxia
Abstract: Lead-free ceramics with high effective energy density ( W rec ), high energy storage efficiency ( η ), and excellent fatigue resistance are crucial for dielectric capacitors. NaNbO3 -ceramics have attracted wide attention because of their excellent performance. Therefore, (1- x ) [0.76NaNbO3 -0.24(Bi0.5 Na0.5 ) TiO3 ]- x SrTiO3 ( x  = 0.01, 0.02, 0.03, 0.04) ceramics with better W rec and high η were gained by a traditional solid-state sintering technology. High E b of 270 kV/cm was obtained via regulating smaller grain size and better density, which is the micro-structure control. (Bi0.5 Na0.5 ) TiO3 and SrTiO3 were incorporated into the NaNbO3 lattice to break the macroscopic ordered domain structure to form a construct polar nanoregions, which is the component-modification control. Finally, an excellent hardness of 6.80 GPa, frequency(5Hz–80Hz), and temperature (25°C–120 °C) stability was also achieved. A moderate W rec of 2.64 J/cm 3, and high η of 89.9% were gained in the 0.97[0.76NaNbO3 -0.24(Bi0.5 Na0.5 ) TiO3 ]-0.03SrTiO3 ceramic. Overall, this work shows that the x  = 0.03 ceramic system can be regarded as the most potential and viable energy storage material.